PERBEDAAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII YANG MEMPEROLEH PEMBELAJARAN DENGAN PROBLEM BASED LEARNING DAN PROBLEM SOLVING - Tuti Erlisa; Suryatul Aini Asyhara; N Noprisa (Universitas Muhammadiyah Lampung, 2021)
The purpose of this study was to determine whether there was a difference in the average learning outcomes of mathematics and which one was the higher average of mathematics learning outcomes between students who used Problem Based Learning and Problem Solving learning methods. This type of research is experimental. The data analysis technique uses the ttes formula. The results show that: (1) there is a difference in the average learning outcomes of mathematics between students who use the Problem Based Learning and Problem Solving learning methods at SMPN 2 Metro, it is known that based on the calculation of the hypothesis test obtained thit = 2.60 and tdaf = 2 ,00 so thit > tdaf. (2) the average learning outcomes of students who use the Problem Based Learning learning method are higher than the Problem Solving learning method in mathematics learning for class VIII.